Situational analysis of syphilis cases taking place between 2015 and 2021 in the state of Rio Grande do Norte - Brazil - Oliveira Assunção, Tereza Beatriz; Rodrigues Veras, Nicolas Vinícius; Leopoldino de Brito Guerra Neto, Custódio; Oliveira Guerra, Ângelo Roncalli; Pereira da Silva, Renivânia; Aparecida da Silva Oliveira, Francimária; Jesus Sodré, Christian; Varela Souza, Wesley Wagner; Matos da Silva, Ana Luiza (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Syphilis is a sexually transmitted infection that represents a severe public health problem worldwide and in Brazil it has not been different. The national compulsory notifications regarding syphilis cases are significantly increasing, and therefore, this fact alone justifies the study of such a relevant subject. Objective: This work presents a situational analysis of syphilis cases in the state of Rio Grande do Norte, Brazil, between 2015 and 2021, aiming primarily at assisting public healthcare authorities in decision-making processes to cope with the disease. Concomitantly, this research aims to build knowledge as well as to provide awareness to the population. Methods: This study analyzed data from compulsory notifications reports from 2015 to 2021, available in the database of the Brazilian Unified Health System’s Informatics Department, in the Brazilian Information System of Notifiable Diseases and in the Brazilian Health Surveillance Secretariat. Results: In the state, 70% of patients with syphilis are aged 15 to 39 years. The rate of patients affected with acquired syphilis that have low education is 48%, and for pregnant women, this value rises to 77%. The declared mixed-race patients represent 48% of notifications for acquired syphilis, and for mixed-race pregnant women, this value increases to 60%. In congenital syphilis, 98% of compulsory notifications occurred for children aged up to 7 days of birth. Conclusion: Syphilis in Rio Grande do Norte is a public health problem that mainly affects the vulnerable population, predominantly the groups at risk with low education, mixed race, and young-adult people, being of paramount importance to combat the disease through population awareness, as well as through constant and adequate compulsory notification.